2020
DOI: 10.1177/0300060520970761
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related long non-coding RNA signature for ovarian cancer

Abstract: Objective Ovarian cancer (OC) affects nearly 22,000 women annually in the United States and ranks fifth in cancer deaths, largely because of being diagnosed at an advanced stage. Autophagy is the cellular process of self-degrading damaged or degenerate proteins and organelles. Long non-coding RNAs (lncRNAs) are a group of RNA molecules whose transcripts are greater than 200 nt but are not translated into proteins. However, just a small number of autophagy-related lncRNAs have been explored in depth. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…Several autophagy related lncRNA signatures predicting the survival of patients have been proven in several cancers, including ovarian cancer, colorectal cancer, hepatocellular carcinoma, bladder urothelial carcinoma, breast cancer, colon adenocarcinoma, and glioma ( Luan et al, 2019 ; Meng et al, 2020 ; Sun et al, 2020 ; Wei et al, 2020 ; Wu et al, 2020 ; Zhou et al, 2020 ; Li et al, 2021 ). However, autophagy related lncRNA prognostic signature has not been investigated in AML.…”
Section: Discussionmentioning
confidence: 99%
“…Several autophagy related lncRNA signatures predicting the survival of patients have been proven in several cancers, including ovarian cancer, colorectal cancer, hepatocellular carcinoma, bladder urothelial carcinoma, breast cancer, colon adenocarcinoma, and glioma ( Luan et al, 2019 ; Meng et al, 2020 ; Sun et al, 2020 ; Wei et al, 2020 ; Wu et al, 2020 ; Zhou et al, 2020 ; Li et al, 2021 ). However, autophagy related lncRNA prognostic signature has not been investigated in AML.…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve suggested that the predictive potential of the risk-score model for OC patients was robust. In benchmark comparisons, the AUC (0.703) was comparable to or better than that of other published gene signatures (AUC: 0.604–0.813) ( Zhou et al, 2016 ; Yang et al, 2017 ; Meng et al, 2020 ; Zhao et al, 2021 ). Univariate and multivariate Cox regression analyses indicated that the risk score was an independent prognostic factor for OC.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, USP30-AS1 is associated with prognosis in bladder cancer (54). This lncRNA was also associated with autophagy in ovarian cancer (55), and was related to immune response in cervical cancer (56) and glioblastoma (57). AL365361.1 was associated with good prognosis and immune response in head and neck squamous cell carcinoma (58) and with early recurrence in hepatocellular carcinoma (35).…”
Section: Discussionmentioning
confidence: 99%